Molecular and Morphological Characterization of the Entomopathogenic Nematode Oscheius cyrus (Nematoda: Rhabditidae) and Molecular Variability of Heterorhabditis bacteriophora from Georgia (Caucasus) - Oleg Gorgadze; Elena Fanelli; Alessio Vovlas; Alberto Troccoli; Eustachio Tarasco; Francesca De Luca (Biology)
Surveys were conducted in the village of Shamgona in the Samegrelo Region of West Georgia, and two nematode species belonging to the Oscheius genus and a population of Heterorhabditis bacteriophora were isolated. Integrative diagnosis, combining morphology, PCA, sequencing and phylogeny, was carried for Oscheius sp. from the soil of hazelnut orchard. This population shows high similarity at morphological and morphometrical levels with O. cyrus from Iran, and the main distinctive features with O. cyrus from Iran are the presence of eight lateral lines and males. Sequence and phylogenetic analyses by using ITS, D2–D3 expansion domains of the 28S rRNA gene, the partial 18S rRNA gene, and the mitochondrial COI confirmed the identification as O. cyrus. A second population of Oscheius sp. and H. bacteriophora was characterized only at the molecular and phylogenetic level. The phylogenetic analyses, based on ITS and D2–D3 expansion domains, revealed the occurrence of O. insectivorus in Georgia grouping with O. insectivorus sequences with high support. The phylogenetic trees of H. bacteriophora, based on D2–D3 expansion domains, ITS, the partial 18S rRNA gene, and mitochondrial COI confirmed the high variability among geographical populations. The present study reports on the occurrence of two species of Oscheius in Georgia for the first time.